Determining the Phosphorus Release Curve for Smizyme TS G5 2,500 Phytase from 500 to 2,500 FTU/kg in Nursery Pig Diets - Katelyn N. Gaffield; Hadley R. Williams; Larissa L. Becker; Jason C. Woodworth; Joel M. DeRouchey; Mike D. Tokach; Robert D. Goodband; Jordan T. Gebhardt; Jill M. Faser (Kansas Agricultural Experiment Station Research Reports, 2022)
A total of 320 pigs (DNA 241 × 600; initially 26.2 ± 0.48 lb BW) were used in a 21-d growth study to determine the available P (aP) release curve for Smizyme TS G5 2,500 (Barentz, Woodbury, MN). At approximately 19 d of age, pigs were weaned, randomly allotted to pens, and fed common starter diets. Pigs were blocked by average pen body weight (BW) and randomly allotted to 1 of 8 dietary treatments on d 18 post-weaning, considered d 0 of the study. Dietary treatments were derived from a single basal diet and ingredients including phytase, monocalcium P, limestone, and sand were added to create the treatment diets. Treatments included 3 diets containing increasing (0.11, 0.19, and 0.27%) inorganic P from monocalcium P, or 5 diets with increasing phytase (500, 1,000, 1,500, 2,000, or 2,500 FTU/kg) added to the diet containing 0.11% aP. All diets were corn-soybean meal-canola meal-based and were formulated to contain 1.24% SID Lys and an analyzed Ca:P ratio of 1.10:1. Prior to the beginning of the study, all pigs were fed a diet containing 0.11% aP for a 2-d period (d 16 to 18 post-weaning). At the conclusion of the study, 1 pig, closest to the mean weight of each pen, was euthanized and the right fibula, rib, and metacarpal were collected to determine bone ash, density, and total bone P. For the overall experimental period, pigs fed increasing inorganic P had improved (quadratic,P≤ 0.053) ADG, ADFI, F/G, and final BW. Pigs fed increasing phytase had improved (quadratic,P≤ 0.004) ADG, F/G, and final BW and increased (linear,P= 0.019) ADFI. For fibula, rib, and metacarpal characteristics, pigs fed increasing levels of aP from inorganic P had increased (linear,P<0.001) bone ash weight, bone ash percentage, bone density, and bone P. Additionally, pigs fed increasing phytase had increased (P<0.05) bone ash weight, bone ash percentage, bone density, and bone P in either a linear or quadratic manner depending upon bone. The available P release curve generated for Smizyme TS G5 2,500 for percentage bone ash is: aP = (0.219 × FTU) ÷ (993.238 + FTU).
Keywords: bone ash; nursery pigs; phosphorus; phytase